Factor that influences the acceptance of halal cosmetic products: a study on consumers in Klang Valley / Halymatun Sa'adiah Abd Rani - Abd Rani, Halymatun Sa'adiah (Faculty of Business and Management, 2018)
According to Arabic term, Halal refers to anything that is permissible under Sharia Law. Allah strictly give a commands for all Muslim to consume what is Halal and leave what is Haram. Halal is not solely focussed on food, but it may extend to all like cosmetics, toiletries, investment, business, banking and finance. After the growth of Halal food and Islamic Bank, Halal cosmetic product has been take place with the high level of demand in Malaysia, Indonesia, and the Middle East. All the cosmetic product must followed the guideline by Jabatan Kemajuan Islam Malaysia (JAKIM) and National Pharmaceutical Regulatory Agency (NPRA). Unfortunately, there have several product that has been announced as prohibited to consume due to contained element like mercury, hydroquinone and tretinoin which lead to self-destruction and violation of Islamic teaching. National Consumer Complaint Centre of Malaysia (NCCC) had received many complaint from consumer with reports had side effect due to the use artificial cosmetics. It became the motivation to identify whether knowledge, religiosity, attitude and intention can be factors to influences on the acceptance of Halal cosmetic products. This study is done to distribute 82 of questionnaires with close ended question by using non-probability convenience sampling. This study are done to analyse all data in using frequency analysis, descriptive analysis, normality test, factor analysis, reliability, correlation and regression test. The findings of the study shows the relationship between attitudes is significant, but there are not significant on knowledge, religiosity and intention in acceptance Halal cosmetic products.